Anxiety, its relation to symptoms severity and anxiety sensitivity in sarcoidosis - Holas, Pawel; Krejtz, Izabela; Urbankowski, Tomasz; Skowyra, Artur; Ludwiniak, Anna; Domagala-Kulawik, Joanna (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background. Sarcoidosis is a chronic systemic granulomatous disease of unknown etiology. Previ-ous studies demonstrated that patients with sarcoidosis had high rates of depression and anxiety, and high magnitude of stressful life events. To date, however, studies have not examined the anxi-ety sensitivity in sarcoid patients and the relationship between psychopathology and symptomse-verity of sarcoidosis.The aims of this study were to evaluate prevalence of depression and anxiety in sarcoid patients, to assess their relationship with the disease symptom severity, and to investigate the relationship between sarcoidosis and anxiety sensitivity. Methods:Thirty three sarcoid patients and thirty three control subjects completed the following:Hospital Anxiety and Depression Scale, Anxiety Sensitivity Index-3. Results: The prevalence of depression (29%) and anxiety (31%) was high among patients and comparable to results from other research groups. Anxiety was significantly correlated with symptom severity and was the main covariate of physical symptoms reported by sarcoid patients. Patients exhibited an increase of their total anxiety sensitivity index and had an increased number of physical concerns.Conclusions: These data confirmed earlier reports that anxiety and depression are common in patients with sarcoidosis and expanded on the previous results by showing that patients exhibited increased anxiety sensitivity and a fear of physical sensations. These results, together with the findings that anxiety was associated with sarcoidosis symptom severity, suggest that targeting anxiety and the physical health concerns may be important in the diagnosis and management of this disease.